Architecture expression: Synthesized architectural expressions in Mayor’s office building of Kupang City - Lake, Reginaldo Christophori; Arinto, Fransiscus X. Eddy; Purbadi, Yohanes Djarot; Dwisusanto, Yohanes Basuki; Bin Toni, Elvis Albertus; Rayawulan, Robertus Mas (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2020)
Efforts to display the expression of the functions and local identities of buildings are merely copying ornamental variations of vernacular architectural elements. As a result, the relation among function-form-meaning remain unseen. This study aims to explain the application of the concept of synthesized architectural expressions on government owned buildings. Based on the research objectives, the Mayor’s office building of Kupang City was chosen as the object of this case study. The initial step of this research is to elaborate the theory of archetypal anatomy and the relation of architectural function-meaning-functions. Furthermore, the observation unit is redrawn in three dimensions and analyzed based on ordering principle of balance and orientation. The analysis shows that the interpretation of the appearance of Mayor's office building of Kupang City displays monumental, formal, local expressions and represents democratic ideologies. Interpretation of synthesized expressions occurs in the dominant aspects of local architecture in the elements of the roof, walls and entrance columns. The results of this study confirm that the concept of synthesized expression plays an important role in the midst of change pressure and for the sustainability of architecture nowadays. DOI: https://doi.org/10.26905/lw.v12i2.4302